2020
DOI: 10.1177/0961203320935518
|View full text |Cite
|
Sign up to set email alerts
|

Sexual dysfunction in Egyptian females with systemic lupus erythematosus: a cross sectional study

Abstract: Objectives Sexual dysfunction in systemic lupus erythematous (SLE) patients is an important issue to be tackled. We aimed to study the prevalence of sexual dysfunction in SLE women and detect its association with depression, functional disability and quality of life. Methods This study included 94 SLE females. Ninety-eight control females agreed to participate. Patients and controls answered a written form… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…Among the eight studies, 758 SLE patients and 1724 healthy individuals in the control group were ultimately enrolled in the meta-analysis. 12,15,16,1923 Six studies reported the prevalence of SD in females and two were aimed towards SD in males. Methods for SD assessment were contrasting.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the eight studies, 758 SLE patients and 1724 healthy individuals in the control group were ultimately enrolled in the meta-analysis. 12,15,16,1923 Six studies reported the prevalence of SD in females and two were aimed towards SD in males. Methods for SD assessment were contrasting.…”
Section: Resultsmentioning
confidence: 99%
“…Patients with SLE often have a lower quality of life, higher level of depression and anxiety, and more negative attitudes towards their body image. 2,39,40 A recent Indian study conducted by Pinto and his colleagues showed that when factors such as a higher dose of steroids and disease activity were disregarded, it becomes apparent that depression, anxiety, and marital satisfaction might impair the sexual function of SLE patients. 41 According to the study of Boomsma et al., 14% of SLE patients reported suicidal ideation, while half of them described that their disease had a great impact on their daily lifestyles.…”
Section: Discussionmentioning
confidence: 99%
“…A total of 367 records were retrieved from the 3 aforementioned electronic databases. Five studies that involved 710 women with SLE and 2,059 healthy women were finally included in the meta-analysis [12][13][14][15][16]. The flow diagram for study selection is presented in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies [ 9 12 , 14 ] have found that several factors were associated with female sexual problems in SLE patients, such as age, number of children, marital satisfaction, economic status, pain, disease duration, disease activity, certain psychological problems like depression and anxiety, functional status, and quality of life. Other factors such as higher dose of steroids also possibly result in female sexual problems [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…A recent meta-analysis [8] revealed the rate of sexual dysfunction (SD) in SLE patients, ranging from 15% to 85.9%, which indicated the severity of the poor assessment and management of these issues. Over the past several years, only a handful of studies [9][10][11][12] used a validated tool of the Female Sexual Function Index (FSFI) to explore the relationship between SLE and sexual problems, demonstrating that SLE was associated with an increased risk of female sexual problems. Tseng et al [13] have reported that 52.5% have sexual problems in Taiwan SLE patients.…”
Section: Introductionmentioning
confidence: 99%